1979
DOI: 10.1093/bja/51.5.417
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity of Inhalation Anaesthetics: Trichloroethylene, Divinyl Ether, Nitrous Oxide and Cyclopropane *

Abstract: SUMMARYThe mutagenic potential of trichloroethylene, divinyl ether, nitrous oxide and cyclopropane was assessed in vitro by microbial assay employing two histidine-dependent strains of Salmonella typhimurium, TA1535 and TA100. Anaesthetic agents in various concentrations were incubated with bacteria in the presence or absence of an enzyme system prepared from enzyme-induced rat liver. Nitrous oxide and cyclopropane were not mutagenic, whereas divinyl ether gave a strongly positive response. Results for trichlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Extensive investigations were conducted to evaluate the effects of inhalatory anesthetics on the embryotoxic, teratogenic, mutagenic and carcinogenic effects when administered in anesthetic concentrations [4,5,9].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive investigations were conducted to evaluate the effects of inhalatory anesthetics on the embryotoxic, teratogenic, mutagenic and carcinogenic effects when administered in anesthetic concentrations [4,5,9].…”
Section: Introductionmentioning
confidence: 99%
“…SCE/eell and transformed variable, y, in lymphoeytes of 38 female dentists, 74 ehairside assistants and 30 male dentists. Mean value, standard error ofthe mean (SEM) and range are shown for eaeh ofthe groups deseribed in Table 1 ide by this test, lhe responses were negative both with Salmonella typhimurium stt-ains, which are sensitive to base-pair mutation, and to fratnc-shift mutation (18,19), Examination of SCE is used inci-easingly in mutagenicity tests comprising mammalian cells. SCE involves an exchange of DNA segments between the two sister chromatids in a chromosome during cell replication, and although the molecular mechanism leading to SCE formation is not fully understood, it is believed to rellect damage of the DNA material.…”
Section: Discussionmentioning
confidence: 99%
“…Baden et al (1979) and Waskell (I978) tested TCE under different experimental conditions for mutagenicity and concluded that TCE was a weak or nonmutagen. No effects of TCE on SCE in Chinese hamster ovary cells have been observed by Stevens et al (1977).…”
Section: Mutagenicity and Carcinogenicitymentioning
confidence: 99%